Evaluasi Usabilitas Aplikasi “SIGERAK” Sebagai Media Pembelajaran Interaktif Menggunakan System Usability Scale (SUS) - Naiya, Rara Weinita; Azwardi, Azwardi; Saputra, Ariansyah (TIN: Terapan Informatika Nusantara, 2025)
Digital learning media has become one of the alternative solutions to address the challenges of 21st-century education, especially in delivering abstract material such as the human movement system at the elementary school level. This study was conducted to design and assess the feasibility of the SIGERAK application as an interactive digital learning medium. The application is equipped with instructional content, quizzes, and educational mini games designed to enhance students understanding of the human movement concept. The trial was carried out at SD Negeri 85 Palembang using a descriptive quantitative approach. A total of 30 students and 2 sixth-grade teachers participated in the learning sessions using the application. The evaluation process employed the System Usability Scale (SUS) instrument, which consists of 10 Likert scale statements to assess aspects of user comfort and ease of use. The collected data were analyzed through score conversion and interpreted based on three dimensions Acceptability Ranges, Grade Scale, and Adjective Ratings. The evaluation results showed that SIGERAK obtained an average score of 80.63. This score falls into the Acceptable category, corresponds to Grade B, and is classified as Good. This study indicates that SIGERAK has a high level of usability and is considered suitable as a game-based thematic learning medium at the elementary school level.